Intellektuelle Anschauung und realer Verstandesgebrauch in Kants Inauguraldissertation - Pfeiffer, Robert (Faculdade de Filosofia e Ciências, 2021)
I will reinterpret the term ‘real use of the understanding’ in the outcome of the suspension of intellectual intuition. Kant applied both terms for the first time in the inaugural dissertation. The ‘objects’ of this use of the understanding thus obtain a more critical meaning and are transformed from substances to functions. Nevertheless, there is still a decisive difference between the inaugural dissertation and the critique of pure reason. Kant shifted his perspective rather than his subject. The question concerning facts (quid facti) turns into the question concerning legal matters (quid iuris). However, ‘noumena’ are no substances which exist independently of consciousness in the inaugural dissertation. Therefore, they must retain a critical meaning even after the Copernican turn. This essay aims to highlight this critical meaning by focusing on the reflective figure of intellectual intuition in the inaugural dissertatio.